Elevated serum C1q is an independent predictor of high residual platelet reactivity in CAD patients receiving clopidogrel therapy - Zhao, Zehao; Ma, Meishi; Huang, Xin; Sun, Tienan; Han, Kangning; Yang, Shiwei; Zhou, Yujie (Frontiers in Immunology, 2022)
Background: Inflammation increases the risk of thrombosis in coronary artery disease (CAD) patients and affects antiplatelet efficacy of clopidogrel. C1q interacts with platelets to activate platelets and induce thrombosis by participating in and regulating the inflammatory response. Whether C1q affects adenosine diphosphate (ADP)-induced platelet reactivity during clopidogrel therapy was unclear and our study aimed to explore the issue. Method: We enrolled 1334 CAD patients receiving clopidogrel therapy and evaluated the association between C1q level and high on-treatment platelet reactivity (HRPR) using logistic regression and restricted cubic spline (RCS). HRPR was defined as ADP-induced maximum amplitude (MAADP) > 47mm plus ADP-induced platelet aggregation (ADPi) < 50%. Results: 516 patients (38.7%) performed HRPR. The frequency of HRPR increases with C1q level elevating (26.3%, 38.4%, 43.2%, 46.7% for 1st to 4th quartile of C1q). The results of multivariate logistic regression demonstrated elevated C1q as an independent predictor for HRPR (2nd quartile: OR = 1.722, 95% CI 1.215-2.440; 3rd quartile: OR = 2.015, 95% CI 1.413-2.874; 4th quartile: OR = 2.362, 95% CI 1.631-3.421, compared to 1st quartile). Restricted cubic spline depicted the nonlinear relationship between C1q and HRPR risk (P for non-linear < 0.05). Conclusion: Current research is the first to explore the association of C1q and ADP-induced platelet reactivity and to demonstrate elevated C1q as an independent risk factor for HRPR in CAD patients during clopidogrel therapy.